2014
DOI: 10.1016/j.bbamem.2014.08.015
|View full text |Cite
|
Sign up to set email alerts
|

A new gating site in human aquaporin-4: Insights from molecular dynamics simulations

Abstract: Aquaporin-4 (AQP4) is the predominant water channel in different organs and tissues. An alteration of its physiological functioning is responsible for several disorders of water regulation and, thus, is considered an attractive target with a promising therapeutic and diagnostic potential. Molecular dynamics (MD) simulations performed on the AQP4 tetramer embedded in a bilayer of lipid molecules allowed us to analyze the role of spontaneous fluctuations occurring inside the pore. Following the approach by Hashi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
72
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(79 citation statements)
references
References 63 publications
7
72
0
Order By: Relevance
“…3) in the same way as for PfAQP, predicting an Arrhenius activation barrier of 3.4±0.6 kcal/mol for water transport that is in agreement with the experimental value of 3 kcal/mol[23] and consistent with recent in silico studies of AQP4. [31, 32] The agreement between this in silico prediction and the in vitro studies of AQPZ should strongly indicate the validity of the approach of this work.…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…3) in the same way as for PfAQP, predicting an Arrhenius activation barrier of 3.4±0.6 kcal/mol for water transport that is in agreement with the experimental value of 3 kcal/mol[23] and consistent with recent in silico studies of AQP4. [31, 32] The agreement between this in silico prediction and the in vitro studies of AQPZ should strongly indicate the validity of the approach of this work.…”
Section: Resultssupporting
confidence: 65%
“…S1), similar to Refs. [31, 32]. The PfAQP-membrane system with glycerols was fully described in Ref.…”
Section: Methodsmentioning
confidence: 99%
“…The trigger for this gating mechanism has not been described; in addition, this in silico approach has not been so far experimentally validated. A similar gating mechanism for human AQP4 was recently described [34], where two putative gate regions formed by two residues on the cytoplasmic side (His95 and Cys178) and the other two on the SF region (Arg216 and His201) modulate opening and closure of the AQP4 pore along four possible conformational states. The relative stability of the two resulting states, open and closed, may depend on small changes in the microenvironment, such as variations of pH.…”
Section: Resultsmentioning
confidence: 71%
“…In a previous study [26], we found that two different gating mechanisms can exist inside the water pore of WT. One is associated with the well-known selectivity filter (SF) on the extracellular side (residues H201 and R216); the other to the spontaneous reorientation of the imidazole ring of a histidine from loop B (H95) enabling an H-bond interaction with a cysteine belonging to the loop D (C178) at the cytoplasmic end (CE).…”
Section: Computation Of the Osmotic Permeabilitymentioning
confidence: 98%
“…The longer simulation time allowed us to identify the reorientation of the side chain of T62 as a key element for epitope recognition and thus for NMO-IgG binding. In recent years molecular dynamics (MD) simulations proved effective to obtain important structural and mechanistic insights into the water transport of aquaporins [26][27][28][29][30][31][32][33]. Here, we employ the same technique to obtain some insight on NMO-IgG epitope reorganization.…”
Section: Introductionmentioning
confidence: 95%